Systems thinking in sustainable agriculture development: a case study of garlic production in Indonesia - Puspitasari; Nurmalina, Rita; Hariyadi; Agustian, Adang (Frontiers in Sustainable Food Systems, 2024)
Sustainable agriculture involves complex interactions among social, economic, and ecological dimensions, each with distinct interests and goals. Achieving sustainable agricultural development is challenging and requires a comprehensive response. This study focuses on Indonesia’s garlic production, employing a systems thinking approach to provide a holistic understanding of the interconnected factors influencing sustainable agricultural systems. We utilized the first two steps of the five-step systems thinking methodology—problem articulation and the formulation of dynamic hypotheses. This process involved developing a causal loop diagram (CLD) to represent the dynamic hypotheses and identifying system archetypes to determine leverage and potential intervention points. Our analysis identified three system archetypes—Drifting Goals, Fixes that Fail, and Limit to Growth—as key patterns influencing the sustainability of garlic production. The Drifting Goals archetype reveals that efforts to boost local garlic stock in Indonesia are hindered by the allocation of garlic for seeds, due to the lack of a clear distinction between garlic for consumption and seed. The Fixes that Fail archetype illustrates the long-term detrimental effects of short-term agricultural practices, such as the overuse of chemical fertilizers and pesticides. The Limit to Growth archetype underscores the critical need for enhanced market access and a shift in consumer preferences to sustain garlic farming. To address these challenges, we recommend establishing clear distinctions between garlic for consumption and seed production, developing the seed industry, promoting integrated pest management, and reducing reliance on chemical inputs through environmentally friendly technology. Additionally, ensuring market and price stability is vital to maintain farmers’ interest in garlic cultivation. Therefore, the government should prioritize market penetration for local garlic and consistently enforce import restrictions to ensure the sustainability of garlic production in Indonesia.